1996
DOI: 10.1111/j.1399-3054.1996.tb00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic growth and carbon allocation in Quercus robur. Sucrose metabolizing enzymes in leaves

Abstract: The high sucrose phosphate synthase (SPS) capacity and the low soluble acid invertase activity of mature leaves of the first flush of leaves remained stable during second flush development. Conversely, fluctuations of sucrose synthase (SS) activity were in parallel with the sucrose requirement of the second flush. Sucrose synthase activity (synthesis direction) in first flush leaves could increase in ‘response’ to sink demand constituted by the second flush growth. Only the ptotosynthates provided by flush mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Carbohydrate reserves of the first flush stems and accorns are necessary to insure the second flush expansion (Alaoui-Sossé et al 1994). At the end of this growth period, they have to be restored in stem compartments from photoassimilate supply (Alaoui-Sossé et al 1994).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Carbohydrate reserves of the first flush stems and accorns are necessary to insure the second flush expansion (Alaoui-Sossé et al 1994). At the end of this growth period, they have to be restored in stem compartments from photoassimilate supply (Alaoui-Sossé et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…At the end of this growth period, they have to be restored in stem compartments from photoassimilate supply (Alaoui-Sossé et al 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in June) are relatively high as compared to herbal plants growing under warm conditions; they rather resemble values found in chilled plants with sink limitation of growth (Brüggemann et al 1992b). In a study on sucrose metabolism in growing Q. robur saplings, Alaoui-Sossé et al (1996) reported that first flush (source) leaves revealed sucrose concentrations of 50-60 mg g -1 dry matter during the development of the second flush (sink) leaves, which can be converted to approximately 50-60 lmol hexose units g -1 fw, the units used in our analysis.…”
Section: Discussionmentioning
confidence: 99%